Farmers Innovative Water Storage System in Agroforestry: A Path to Prosperity - Chavan, Sangram Bhanudas (Indian Journal of Agroforestry, 2025)
Tree farming under climate change scenarios has become a reliable source of income, as multiple abiotic stresses negatively impact agricultural yield and increase losses by up to 70%. The hardy nature of tree species enables them to survive under harsh conditions, aiding in adaptation and mitigation of extreme climatic events. In this context, planting trees in agricultural lands as part of agroforestry has emerged as a promising strategy.